(untitled) (International Journal of Ayurveda and Pharma Research, 2021)
Today the desk/chair-hand combination became the cultural norm in the workplace. Typical seated worker has risk of musculo-skeltal disorders same as lifting heavy weights on job. CTS is one of the musculo-skeletal disorder and is due to overuse, strain, forceful or stressed motion of hand and wrist. Activities or jobs that require repetitive flexion and extension of the wrist may contribute such as computer work, sewing, writing, playing instruments, and driving for long duration. Its Risk factors include RA or other wrist arthritis, Diabetes etc. In Ayurveda increase or vitiation of Vata results in compression and pain which is present in CTS. Ayurveda management of Carpal tunnel syndrome involves the management of vitiated Vata Dosha. The primary aim is to ease inflammation and pain by improving blood circulation and relaxing the muscles. In this regard, an attempt has been made to review the Ganas (Group of drugs) like Vednasthapana, Daha-Shamaka and therapies like Basti, Swedna mentioned in Ayurvedic classical texts and scientific journals which helps in management of symptom and eliminate the root cause of diseases.